Label Produk, Iklan Emosional, dan Diskon serta Pengaruhnya terhadap Keputusan Pembelian - Muhammad Akbar Marzuq; Anik Lestari Andjarwati (UNESA In Collaboration With APSMBI (Aliansi Program Studi dan Bisnis Indonesia), 2020)
A brand will carry out several marketing strategies to attract consumers. especially for countries with a Muslim majority community, the product must have halal legality. There are several factors considered by consumers to choose the product purchased, among others, the existence of halal labels on packaging, emotional advertising, and diskons. The purpose of this paper is to study the effect of product labels, emotional advertising, and discount on purchasing decisions. This research is focused on consumers who have bought Chatime as a bubble drink, Muslim, aged 15-60 years old, and a final consumer. uses a nonprobability sampling technique. Questionnaires were distributed to 200 participants with Google form. Data analysis techniques using Multiple Linear Regression. The results showed that product labels, iklan emosional, and diskons had a positive effect on consumer purchasing decisions.